2011
DOI: 10.1590/s0100-83582011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento do banco de sementes de plantas daninhas em áreas com Cana-de-Açúcar colhida mecanicamente

Abstract: O objetivo deste trabalho foi monitorar o banco de sementes de área cultivada com cana-de-açúcar colhida mecanicamente por seis anos e um ano, utilizando-se técnicas de agricultura de precisão. As amostragens de solo para determinação do banco de sementes foram realizadas utilizando-se grade amostral regular de 1,6 ha. Os mapas de infestação foram obtidos pela técnica de interpolação por krigagem. Observou-se que o talhão de cana colhida mecanicamente por seis anos apresentou menor potencial de infestação de v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
8
0
8
Order By: Relevance
“…The burning of sugarcane plantations, ordinary activity in the past, has been losing importance, due to society pressures and legal requirements, which lead to the prohibition of sugarcane plantation burning, as in the state of São Paulo, that follows scheme of progressive legal restrictions -20% by 2010; 30% by 2012; 50% by 2014; 80% by 2018; and 100% by 2020 (Monquero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burning of sugarcane plantations, ordinary activity in the past, has been losing importance, due to society pressures and legal requirements, which lead to the prohibition of sugarcane plantation burning, as in the state of São Paulo, that follows scheme of progressive legal restrictions -20% by 2010; 30% by 2012; 50% by 2014; 80% by 2018; and 100% by 2020 (Monquero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that morning glory species, before with little expression, are among the main ones on environment provided for mechanized harvesting (Monquero et al, 2011;Ferreira et al, 2010;Kuva et al, 2007). The growing importance of Ipomoea plants in sugarcane fields increases the need for information on the biology of these plants in ratoon sugarcane cycle, given the enrichment of the seed bank with species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…A Agricultura de Precisão considera a variabilidade dos fatores que interferem na produtividade das culturas, esta técnica do estudo da variabilidade espacial concentrou-se na Ciência do Solo (MONTANARI et al, 2012). No entanto, atualmente este conceito tem sido perfeitamente extrapolado para a Ciência das Plantas Daninhas.…”
Section: Introductionunclassified
“…Weed tests included ten selected plant species, belonging to five botanical families, based on bibliographic survey, according to their importance in the sugarcane sector (Oliveira and Freitas, 2008;Monquero et al, 2011a). They are: Convolvulaceae: little bell (Ipomoea triloba) and Merremia aegyptia; Curcubitaceae: sponge gourd (Luffa aegyptiaca); Euphorbiaceae: Mexican fireplant (Euphorbia heterophylla) and castorbean plant (Ricinus communis); Fabaceae: showy rattlebox (Crotalaria spectabilis) and velvet bean (Mucuna aterrima); and Poaceae: windmill grass (Chloris polydactyla), crabgrass (Digitaria horizontalis) and signalgrass (Urochloa decumbens).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, control effectiveness over nematodes depends on a detailed survey about the main weed species that host these phytoparasites. This problem becomes extremely relevant, since studies on this area are scarce (Rizzardi et al, 2003) and, mostly, do not cover weeds that became recurrent in sugarcane cultures after the implementation of mechanized harvest system (Monquero et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%